(untitled) (Editora Impacto Científico, 2025)
Brazil faces structural challenges in combating the smuggling of electronic devices, such as TV Boxes, which enter the country without certification and are often used for illicit access to paid content. Once seized, these devices become technological and environmental liabilities. At the same time, inequalities persist in access to digital technologies, especially in public schools in low-income regions, exacerbating educational disparities. In this scenario, the Recriar Project from the State University of Northern Paraná (UENP) has emerged, proposing the reuse of seized TV Boxes as reconfigured educational tools. The initiative combines sustainability, digital inclusion and innovation, contributing to social transformation and the democratization of access to digital culture.